CHED-UNIFAST PROFILING AND BILLING CABINET - Alcarde, Jerwin G. (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
Republic Act No. 10931 intends to provide all Filipinos with an equal opportunity to quality tertiary education as to ensure the optimized utilization of government resources in education. This study was designed and develop the system Commission on Higher Education-Unified Financial Assistance System for Tertiary Education Profiling and Billing Cabinet to effectively and efficiently deliver processes in the aspect of student profiling and billing documents that was an integral part after the enrolment period. This system will be utilized as system process that could helped the Registrar and Accountant to generate reportorial accurately. The respondents of the study were three (3) campus registrars, three (3) campus accountants , two (2) staff and two (2) IT Experts who are purposively selected. This study applied the Unified Modeling Language (UML) to describe the structure of the software. Likewise, using the Agile Method by (Dinni Muslihat, 2018) as guide in developing the system. The International Organization for Standardization (ISO) 25010:2011 software engineering standard was used to evaluate the application in terms of product quality in use criteria and all mean equivalents for each characteristic were described as “Very Effective”. The study proved that the system is useful and effective.